Rolul organizaţiilor mutuale în cadrul asociativ pentru vârsta a treia în România - Lambru, Mihaela (Calitatea Vieții, 2011)
In the last years, the policy debates around the complex issues of social services for old age have increased in Romania. As in many other social services areas, the nongovernmental organizations represent a valid option for service delivery. The present article has a double aim: to present the specific features of the nongovernmental organizations active in the area of old age and, at the same time, to propose a typology of the organizations involved in various service areas for old age, in Romania. Among those identified organizations, an important role is covered by mutual aid associations for pensioners (CARP), associative structures belonging to the social economy sector, and representing an interesting solution for various challenges determined by the evolution of the Welfare State in Romania.